الشراكة المجتمعية في اتخاذ القرارات كمؤشر لعملية تنموية محلية ناجحة - بوعمامة، فايزة (جامعة قاصدي مرباح - ورقلة, 2017)
Participation has become a central issue in the development plans for its human mobilization, acceptance of innovations, support and assimilation, considering the society and its development as an educational process aimed at carrying out actions that will help people to achieve the goals in a democratic manner so that community leaders become constructive factors in learning experiences and Are not just fans to improve the social conditions, it also helps the community to the optimal use of the energies and capabilities of its members and groups and give the opportunity for marginalized groups in society for development and advancement, this study was to clarify the role played by participation in dynamic activation Development.
غدت المشاركة من القضايا المحورية في خطط التنمية لما تتضمنه من التعبئة البشرية وتقبل التجديدات ودعمها واستيعابها فتنظر إلى المجتمع وتنميته على أنها عملية تعليمية تستهدف القيام بإجراءات، من شأنها مساعدة الناس على تحقيق الأهداف بأسلوب ديمقراطي فتصبح قيادات المجتمع عوامل بناءة في تعلم الخبرات وليس مجرد مشجعين لتحسين الظروف الاجتماعية، كما أنها تساعد المجتمع على الاستخدام الأمثل لطاقات وقدرات أفراده وجماعاته وتعطي الفرصة للفئات المهمشة في المجتمع من اجل التطور والرقي، فهذه الدراسة جاءت لتوضيح الدور الذي تلعبه المشاركة في تفعيل ديناميكية التنمية.
Keywords: الديمقراطية التشاركية -- المشاركة المجتمعية -- التنمية المحلية